Projeto LUPA: Laboratório urbano pela arte - Andreia Fernandes; Andrea Monteiro Vicente; Alice Batista; Cláudia Silva (Midas: Museus e Estudos Interdisciplinares)
In ‘Educación 2021: Para una Historia del Futuro’, Nóvoa introduces the concept of public space for education, a scenario in which school systems and societies share responsibility for education. The educational project LUPA originated in this context – a volunteer-led, non-formal educational service of an experimental nature, without funding and without a budget, directed primarily to the community of Castelo Branco. Through education through art it aims to reflect upon the relationship between the city as a physical space and the community as a social space, with the premise that the city is the starting point for the promotion, operation and construction of urban identity, underscoring the value of empathy with culture and arts, and building spaces which function as laboratories to share, experience and create. This project, still in its first year, is organized into monthly activities/labs, that intend to (re)known/(re)value the tangible and intangible heritage of Castelo Branco, or albicastrense. Starting with an analysis of the educational and cultural offer in the region, and the diagnosis and identification of missing elements, an experimental project is set up, its goals and flexible actions following assertive methodologies that encourage partnerships between cultural and educational institutions.